Development of electronic handouts for class X high school ecosystem materials for online learning - Jeklin Hutagaol; Ervan Johan Wicaksana; Jodion Siburian (Jurnal Inovasi Pendidikan IPA, 2022)
Students' low interest is the most common problem in online learning. As a solution, we need media that is attractive and easy to use. This study aims to (1) develop electronic handouts on the Ecosystem topic for class 10th-grade senior high school for online learning, (2) determine the feasibility of handouts, (3) determine teacher perceptions of handouts, and (4) determine student perceptions after using handouts in learning. This study uses a 4D development model. The subjects of this study were 10th-grade high school students consisting of small groups (6 students) and large groups (26 students). The results of this study indicate that the validity of the material reaches a percentage of 90% in the "very good" category, the validity of the media reaches a percentage of 95% in the " very good " category, the teacher's perception results in the percentage of 90.83% in the "very good" category, the percentage of satisfaction is average. The small group average was 89.72% in the "very satisfied" category, and the average satisfaction percentage for the large group was 90.12% in the "very satisfied" category. So it can be concluded that electronic handouts can be used in online learning. This research handout can be used as an alternative learning resource to increase students' interest in learning.